This research imes to determine whether dyspepsia is a serious problem for our society. The frequency of dyspepsia has been explored in different parts of the societ in Ankara - Nazmiye KOYUNCU; Özden UZUNALİMOĞLU and Kadir BAHAR and Fahri IŞITIN and Hayri KARAASLAN and Alp TANRIVERDİ and Aydın YAĞMURLU and Günay ŞAHİN and Sevil KOÇAK and Mutlu MEYDANLI and et al. (Turkish Journal of Gastroenterology, 2020)
-